Weekly Hippotherapy Improves Gross Motor Function in Cerebral Palsy: A Meta-Analysis: Evidence on Weekly Therapy Dosage in Children With Cerebral Palsy - I Nyoman Windiana; Komang Alit Gita Andhira; Kadek Surya Candra Wijaya; I Gusti Agung Ayu Pramasinthya Aguseny Yudana (Universitas Pendidikan Ganesha, 2026)
Current clinical practice guidelines have not specifically addressed the roles of physiotherapy and occupational therapy in enhancing physical function during activities in children with cerebral palsy. Nonetheless, hippotherapy, which utilizes equine movement as a therapeutic modality, has shown promise as an adjunctive intervention for improving gross motor function in this population. This meta-analysis aims to assess the therapeutic effects of weekly hippotherapy sessions on gross motor function in children diagnosed with cerebral palsy. A systematic review was conducted according to PRISMA guidelines. Searches were performed on Google Scholar, PubMed, and Scopus databases for randomized controlled trials (RCTs) evaluating the impact of weekly hippotherapy on children with cerebral palsy. The methodological quality of included studies was assessed using the Cochrane Risk of Bias 2 (ROB-2) tool. Five RCTs involving a total of 203 children with cerebral palsy met the inclusion criteria. Meta-analysis using random-effects models demonstrated significant improvements in gross motor function following weekly hippotherapy sessions (SMD, 0.44; 95% CI, 0.04-0.85; P = 0.03). Study heterogeneity was moderate (I2 = 57%). Weekly hippotherapy sessions significantly enhance gross motor function in children with cerebral palsy compared to controls. These findings support the inclusion of hippotherapy in comprehensive rehabilitation programs aimed at optimizing motor skill development. Further research is needed to establish standardized treatment protocols and examine long-term outcomes.